Wearable Textile Antenna On Electromagnetic Band Gap (EBG) For Wlan Applications - Mohamad Isa, Mohd Sa'ari; Azmi, Aini Noor Liana; Azmi , Awang Md Isa; Md Saat, Mohd Shakir; Abu, Maisarah; Ahmad, Azlinda (Penerbit Universiti, UTeM, 2014)
-